pOpsicle: An all-optical reporter system for synaptic vesicle recycling combining pH-sensitive fluorescent proteins with optogenetic manipulation of neuronal activity - Seidenthal, Marius; Jánosi, Barbara; Rosenkranz, Nils; Schuh, Noah; Elvers, Nora; Willoughby, Miles; Zhao, Xinda; Gottschalk, Alexander (Frontiers in Cellular Neuroscience, 2023)
pH-sensitive fluorescent proteins are widely used to study synaptic vesicle (SV) fusion and recycling. When targeted to the lumen of SVs, fluorescence of these proteins is quenched by the acidic pH. Following SV fusion, they are exposed to extracellular neutral pH, resulting in a fluorescence increase. SV fusion, recycling and acidification can thus be tracked by tagging integral SV proteins with pH-sensitive proteins. Neurotransmission is generally stimulated by electrophysiology, which is not feasible in small, intact animals, thus limiting the approach to cell culture regimes. Previous in vivo approaches depended on distinct (sensory) stimuli, thus limiting the addressable neuron types. To overcome these limitations, we established an all-optical approach to stimulate and visualize SV fusion and recycling. We combined distinct pH-sensitive fluorescent proteins (inserted into the SV protein synaptogyrin) and light-gated channelrhodopsins (ChRs) for optical stimulation, overcoming optical crosstalk and thus enabling an all-optical approach. We generated two different variants of the pH-sensitive optogenetic reporter of vesicle recycling (pOpsicle) and tested them in cholinergic neurons of intact Caenorhabditis elegans nematodes. First, we combined the red fluorescent protein pHuji with the blue-light gated ChR2(H134R), and second, the green fluorescent pHluorin combined with the novel red-shifted ChR ChrimsonSA. In both cases, fluorescence increases were observed after optical stimulation. Increase and subsequent decline of fluorescence was affected by mutations of proteins involved in SV fusion and endocytosis. These results establish pOpsicle as a non-invasive, all-optical approach to investigate different steps of the SV cycle.